Factors Influencing Stock Prices with Inflation as Moderating Variable - Jessica Husni; Henryanto Wijaya (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this research is for specifying the impact of profitability ratio also solvency ratio on stock prices in manufacturing businesses registered under Indonesia Stock Exchange in 2018-2020 with inflation as moderating variable. The analysis used a method named, purposive sampling for the sample selection, and it was found that there were 72 samples of companies that could be used in the study. The data is processed with the help of the Microsoft Excel 2019 and EViews version 12 application program. The outcome from this research shows profitability ratio with the Return on Assets proxy, solvency ratio with the Debt-to-Equity Ratio proxy, and inflation have a positive also significant impact on the stock prices. Meanwhile, profitability ratio with Return on Equity proxy showed a negative as well as significant impact on the stock prices. Moreover, inflation is known to moderate the effect of profitability ratio for the Return on Assets proxy, profitability ratio for the Return on Equity proxy, and solvency ratio with Debt-to-Equity Ratio proxy to the stock prices.